(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the knowledge of hand, foot and mouth disease prevention of mothers with children under 5 years old in Dai Thanh commune and Tan Thanh commune, Nga Bay city, Hau Giang province in 2024. Subjects and methods: Cross-sectional study with analysis, surveying knowledge of hand, foot and mouth disease prevention of 416 mothers with children under 5 years old, residing in Dai Thanh commune and Tan Thanh commune, Nga Bay city, Hau Giang province from December 2023 to June 2024. Results: 99% of mothers have heard of hand, foot and mouth disease. The percentage of mothers who know the symptoms of the disease includes mild fever (97.4%); blisters the size of chopsticks, gray, red in color on the knees, palms, and soles of the feet (79.1%); fatigue (77.2%)... 96.2% of mothers know that hand, foot and mouth disease is dangerous; 66.3% understand that the cause of the disease is a virus. Only 40.1% know that there is no specific treatment for the disease and 54.8% know that there is no vaccine to prevent the disease. The percentage of mothers who know that the disease is transmitted through the digestive tract (86.1%), toys contaminated with the virus (74.8%), and using water contaminated with the virus (29.1%)... Conclusion: The mothers in the study had general knowledge about hand, foot and mouth disease prevention, accounting for 79.1%. It is necessary to strengthen propaganda work and update knowledge on hand, foot and mouth disease prevention for the community to contribute to reducing the incidence of hand, foot and mouth disease in the locality in particular and the whole country in general.